Prevalence and Predictors of Patient Nonadherence to Pharmacological Acute Pain Therapy at Home After Day Surgery: A Prospective Cohort Study. Issue 2 (16th June 2017) - Stessel, Björn; Theunissen, Maurice; Marcus, Marco A.; Joosten, Elbert A.; van Kuijk, Sander M. J.; Fiddelers, Audrey A. A.; Peters, Madelon L.; Hoofwijk, Daisy M. N.; Buhre, Wolfgang F. F. A.; Gramke, Hans‐Fritz
Abstract: Background: Good adherence to prescribed analgesics can be crucial to suppress or even prevent acute postoperative pain after day surgery. The aim of this study was to analyze prevalence and predictors of analgesic nonadherence after day surgery. Methods: Elective patients scheduled for day surgery were prospectively enrolled from November 2008 to April 2010. Outcome parameters were measured by using questionnaire packages at 2 time points: 1 week preoperatively and 4 days postoperatively. The primary outcome parameter was analgesic nonadherence. Adherence was defined according to the patient's response to the questionnaire item "analgesia use as prescribed": full adherence, "yes"; partial adherence, "yes, sometimes"; nonadherence, "no." Bivariate and multivariate logistic regression analyses were performed to identify predictors of analgesic nonadherence. Results: A total of 1, 248 patients were included. The prevalence rates of analgesic nonadherence and partial adherence were 21.6% and 20.0%, respectively, in the total study population but dropped to 9.4% and 19.8%, respectively, in patients with moderate to severe pain. Low postoperative pain intensity and short duration of surgery were the most important predictors of analgesic nonadherence. The most important preoperative predictors for analgesic nonadherence were low preoperative pain intensity, low preoperative expectations of pain, and low fear of short‐term effects of surgery. Conclusion: Analgesic nonadherence and partial adherence are common after day surgery but decrease as average pain intensity increases. Patients at risk for analgesic nonadherence can be identified during the preoperative period based on preoperative pain intensity, preoperative expectations of pain, and fear of surgery.